Phenotypes of patients with Direct Oral Anticoagulant (DOAC) underdosing in atrial fibrillation: results from the ARENA registry - Brockmüller, Christine; Meid, Andreas; Senges, Jochen; Hochadel, Matthias; Haefeli, Walter E.; Stoll, Felicitas E. (Clinical drug investigation, 2025)
Background and Objectives: Oral anticoagulation in patients with atrial fibrillation is crucial to prevent thrombus formation in the heart, a major cause of ischemic stroke. The appropriate dose of direct oral anticoagulants (DOAC) - either standard or reduced dose - must be chosen individually in accordance with defined patient characteristics. However, a significant proportion of patients receive inappropriately low DOAC doses (underdosing). With a novel medication-based approach, this study aims to facilitate the identification of patients at risk of DOAC underdosing. Methods: The prospective ARENA registry is a multi-centre study on patients with atrial fibrillation in Germany. Patients gave detailed information on medication, including over-the-counter preparations. Medication data were grouped according to the Anatomical Therapeutic Chemical (ATC) classification. In a bivariate analysis, the characteristics of patients on an appropriate versus inappropriate dose were compared (n = 866). To further evaluate variables for their association with underdosing, a model based on ATC third level medication data complemented with dose-adjustment criteria and validated clinical scores in all patients with complete information was built (n = 504). Results: In 15% of patients, an inappropriately low dose was found. The number of DOAC drug interactions, concomitant antiplatelet therapy and the total drug count were the most important predictors of DOAC underdosing. Mineral supplements and better health-related quality of life (HrQoL) were predictive of correct DOAC dosing, among others. Conclusions: Medication-related data showed to be predictive of DOAC underdosing. Clinicians should check for inappropriately reduced DOAC doses, especially in patients undergoing antiplatelet therapy, polypharmacy and reduced HrQoL.
Veröffentlicht: 12. Dezember 2024
Gesehen am 07.03.2025